Underwater cutting of 50 and 60 mm thick stainless steel plates using a 6-kW fiber laser for dismantling nuclear facilities. (July 2019) - Shin, Jae Sung; Oh, Seong Yong; Park, Hyunmin; Kim, Taek-Soo; Lee, Lim; Chung, Chin-Man; Lee, Jonghwan
Highlights: Underwater laser cutting studies on thick stainless steel plates was performed. An underwater cutting head was developed by upgrading our previous head. 50 and 60 mm thick stainless steel plates were cut successfully in water. The cutting performance was the best among the previously reported results. This work will contribute to dismantling nuclear facilities in the future. Abstract: Underwater cutting of 50 and 60 mm thick stainless steel plates with a 6-kW fiber laser was performed as a fundamental study for application to dismantling nuclear facilities. For this purpose, an underwater cutting head was developed by upgrading our previously developed in-air cutting head. A waterproof function was added while the optical design of the in-air cutting head was maintained. In the developed head, a single supersonic minimum length nozzle was applied without any complicated nozzle features because it was enough to make a local-dry-zone. With this head, cutting tests were performed for pierced and non-pierced specimens. The pierced specimen showed a slightly better cutting performance than the non-pierced specimen. However, the cuttings were adequate for both types of specimens with thicknesses of 50 and 60 mm. In the cutting results for the non-pierced specimens, the maximum cutting speeds were 80 mm/min for the 50 mm thickness and 40 mm/min for the 60 mm thickness. To the best of our knowledge, the results from this study show the best cutting performance in terms of speed and thickness for the same laser power among the reported results of underwater laser cutting. The kerf width was also measured for each cutting. As in ordinary laser cutting, the kerf widths were narrow. For the cutting at each maximum speed, the kerf widths for the 50 mm thickness were 1.6 mm for the front surface and 0.7 mm for the rear surface, and the kerf widths for the 60 mm thickness were 1.5 mm for the front surface and 1.2 mm for the rear surface. It is expected that the results of this study will contribute to the continued development of underwater cutting research for dismantling nuclear facilities.